A qualitative study of the long-term consequences and adaptation in daily life after replantation surgery at a young age. (December 2022) - Rosberg, Hans-Eric; Dahlin, Lars B; Carlsson, Ingela K
Introduction: Impaired functioning is seen in patients following replantation surgery to the thumb or fingers. Our aim was to explore long-term consequences and adaptation in daily life after a thumb and/or multiple finger amputation followed by replantation surgery during young age. Methods: Semi-structured interviews were conducted with nine recruited individuals and analysed using content analysis. The participants were asked to describe their hand function, pain, appearance, emotional consequences, impact on daily life and strategies for overcoming daily challenges. Results: The interviews revealed five main categories: memories of the injury and concerns for the future; hand function, pain and cold sensitivity; feelings about having a visibly different hand; adaptation to impairments and challenges in daily life; and key messages to healthcare professions and advice to future patients. The circumstances of the injury were well remembered. Pain at rest was rare but occurred when grasping. Cold sensitivity was a major issue. Appearance-related concerns varied from none to a major problem. Despite impaired hand function, solutions were found to challenges in daily life. Compensatory strategies, personal resources and support from others were important in this adaptation process. Conclusions: Patients with replantation surgery after an amputation during young age adapt to challenges in daily life over time. Healthcare professionals should offer adequate support to enable emotional processing of trauma experience. Appearance-related concerns should be addressed to prevent distress. Information about alleviating strategies to overcome long-term problems with cold sensitivity should be emphasized.